A survey of properties of concrete aggregates from different sources near Metro Manila. - Yamao, Yoshihide (Philippine Engineering Journal)
The influence of aggregate properties on the performance of concrete is well documented in literature. It is important, therefore, that information regarding their properties be determined prior to mixing of concrete. This paper presents the results of tests performed to determine the physical properties of aggregates from different sources near Metro Manila.